Model for the calculation of pressure loss through heavy fuel oil transfer pipelines - Hector Luis Laurencio-Alfonso,; José Falcón-Hernández; Yoalbys Retirado-Mediaceja; Olga Pérez-Maliuk (Minería y Geología, 2012)
Considering the limitations of methodologies and empirical correlations in the evaluation of simultaneous effects produced by viscous and mix strength during the transfer of fluids through pipelines, this article presents the functional relationships that describe the pressure variations for the non-Newtonian fuel oil flowrate. The experimental study was conducted based on a characterization of the rheological behavior of fuel oil and modeling for a pseudoplastic behavior. The resulting model describes temperature changes, viscous friction effects and the effects of blending flow layers; which is therefore the basis of calculation for the selection, evaluation and rationalization of transport of heavy fuel oil by pipelines.